Educational choices of Polish youth in an intergenerational perspective. Issue 4 (19th May 2021) - Pustulka, Paula; Sarnowska, Justyna
ABSTRACT: This article investigates the parental role in educational decisions of young adults in Poland. The country-context is vital due to the profound impact of the 1989 transition on educational aspirations and subsequent 'degree boom' in the younger cohorts. Using data from two qualitative studies, we adopt an intergenerational lens to examine how young men and women are affected by their mothers and fathers when making choices about their educational pathways. We propose a matrix of four types of educational aspirations framed by parents, pointing to the importance of resources (capitals/socialisational conditions) on the one hand, and the notion of socialisation influences linked to pragmatism and experimentation, on the other. Based on the analysis we discuss four ideal-types of Successors, Questers, Trailblazers and Hustlers. Accounting also for the gender dimension, we contribute to the broader debates on the reproduction of inequalities and unpack 'critical moments' in youth transitions.